PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA ULAR TANGGA PADA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD NEGERI 85 LUBUK LINGGAU - Zara Zeti, Shilfa; Fiani, Ani; Asri Purwasi, Lucy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement in Mathematics learning outcomes of fourth-grade students of SD Negeri 85 Lubuk Linggau after using the Teams Games Tournament learning model. This study uses Pre-test and Post-test. Sampling was obtained from the population, the sampling technique in this study was using random sampling. The instrument used was in the form of multiple choices totaling 22 questions. The data analysis technique used the t-test at a significance level of alfa = 0.05. The results of the study obtained that t count = 6.12 > t table = 1.711 so that it is proven that Ha is accepted and Ho is rejected. The improvement in Mathematics learning outcomes of fourth-grade students of SD Negeri 85 Lubuk Linggau after using the Teams Games Tournament learning model was significantly complete. The average value is 80.29 and the percentage of students who completed was 91.66%.